Foliar Nematode Aphelenchoides spp. (Nematoda: Aphelenchida: Aphelenchoididae) - Lindsay Wheeler; William T. Crow (EDIS, 2020)
There are nematodes of several genera that feed on plant stems and foliage, including Aphelenchoides, Bursaphelenchus, Anguina, Ditylenchus and Litylenchus. Herein, we apply the common name “foliar nematode” specifically to plant-feeding nematodes in the genus Aphelechoides, specifically Aphelenchoides besseyi, Aphelenchoides fragariae, and Aphelenchoides ritzemabosi. While most members of Aphelenchoides are fungivorous (feed on fungi), these three species have populations that are facultative plant-parasites that can feed on live plant tissue. Ten other species of Aphelenchoides also are recognized as facultative plant-parasites, but these are not as commonly encountered or as economically significant as the aforementioned species. Unlike most plant-parasitic nematodes, foliar nematodes can infest the aerial portions of plants rather than dwelling strictly in soil and plant roots. Damage from their feeding can reduce yield in food crops and ruin the appearance of ornamentals. https://edis.ifas.ufl.edu/in1279